Morre a empresa privada e nasce a comunidade: memória e territorialidade na comunidade Indígena Projeto Mapi (Médio Solimões-AM) - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This dissertation intends to describe and analyze the processes of territorialization and formation history of the Mapi Project community based on the narratives of the Caixana indigenous agents of the Middle Solimões region, Tefé, Amazonas. The community is connected to the municipality of Tefé by a road of 24 km, called EMADE. The paving of the same and the installation of electric light in the area triggered a process of real estate speculation and since then the area of use of the community has been sold, taken over, invaded by non-indigenous agents. In response to the invasions, the agents of the community started to activate the ethnic identity of the group and began the struggle for the demarcation process of their lands. In 2004 the recognition of the area as indigenous was deferred by the National Indian Foundation (FUNAI) and since then the demarcation is expected. This collective has triggered diverse elements for its ethnic affirmation and in the mobilization of the fight for the territory. It is possible to point out some of them: the revitalization project of the Geral Language (Nheengatu), the narratives of arrival and stay on the land, an indigenous ancestry that is "inherited" from the grandparents, parents and other relatives that live in TIs already demarcated.
Keywords: Povos indígenas - Tefé (AM); Territorialização; Comunidade Indígena Caixana; Etnologia; História e antropologia; CIÊNCIAS HUMANAS: ANTROPOLOGIA: ETNOLOGIA INDÍGENA; Indígenas Caixana; Processos de Territorialização; Conflitos e Memória